RELATIONSHIP BETWEEN PHYSICAL FITNESS AND THE DERMATOGLYPHICS OF GUARD-CIVILIAN LIVES. (Fiep Bulletin - online, 2017)
the relationship between physical fitness and the dermatoglyphics of lifeguards civilians, aimed to correlate thedermatoglíficos drawings of general tips of the fingers with the results of the physical fitness tests applied to candidates for civilianlifeguards 2° fire squad, a total of 21 individuals of both sexes, aged between 18 and 40 years, which was developed in the city of SãoFrancisco do Sul/SC, at the headquarters of the Corporation. We used the dermatoglífico method according to the Protocol ofCummins; Midlo (1942) proposed by Son (1997) as an instrument of research and the variables of the physical fitness test evidencefor lifeguards. For the analysis and interpretation of data obtained was used the descriptive statistics with measures of centraltendency (mean) and dispersion (standard deviation). The data obtained were plotted on an Excel spreadsheet for Windows fordescriptive analysis from the trend and associations. It was possible to check and that those who obtained the best average time inphysical fitness to become Guard Civilian Lives (GVC), were classified as class IV where the lifeguard had a sum of lines in your prints(LONG QT) greater than and less than 162.8 134.2. It was also verified that the individuals of this class have a predominance ofcoordination, resistance of speed and agility in their potentialized physical valences and the potential ones being strength and speed,that is, that they must be improved. From the results, it can be concluded that there is a correlation between physical fitness and digitalanalysis (dermatoglyphia) of the individuals participating in the research.